THE IMPACT OF CELEBRITY ENDORSEMENT ON PURCHASE DECISION OF MS GLOW PRODUCTS, THROUGH BRAND TRUST ON GEN Z FACTORY WORKERS IN JEPARA DISTRICT - Musthofa, Calvin Nuril (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
ABSTRACT Purpose: This study examines the impact of celebrity endorsements on purchase decisions, with brand trust as a mediating variable, in the context of the Indonesian cosmetics industry, specifically MS Glow. Design/methodology/approach: A quantitative research approach was applied, utilizing a sample of 400 Gen Z garment workers in Jepara district. Data were analyzed using Structural Equation Modeling (SEM) with Smart-PLS version 4.0, including outer model testing, inner model testing, mediation testing, and hypothesis testing. Findings: The results indicate that Celebrity Endorsement (X1) has a positive and significant influence on Brand Trust (Z1) and Purchase Decision (Y1). Additionally, Brand Trust (Z1) significantly influences Purchase Decision (Y1). Mediation analysis confirms that Brand Trust (Z1) partially mediates the relationship between Celebrity Endorsement (X1) and Purchase Decision (Y1). Research limitations/implications: This study is limited to Gen Z garment workers in Jepara, which may restrict generalizability to other demographics or regions. Future research could explore different age groups or industries. Practical implications: The findings provide insights for cosmetic brands on leveraging celebrity endorsements to enhance brand trust and influence consumer purchase decisions. Originality/value: This study contributes to the literature by empirically validating the mediating role of brand trust in the relationship between celebrity endorsement and purchase decision, specifically in the Indonesian cosmetics market. Paper type: Research paper Keyword: Celebrity endorsement, brand trust, purchase decision